Communication Strategies Used by the English Teacher in Teaching Speaking Skill - Jumiati Jumiati; Sofyan A Gani; Diana Fauzia Sari (Research in English and Education Journal, 2017)
Communication strategies have a big role in learning target language since they can be the tool in solving communication problem. Both teacher and students need to use the strategies in communicating to keep the conversation flow smoothly. This study aimed to find out the types of communication strategies used by the English teacher during the teaching process and to explain the implementation of those strategies in the classroom. By implementing Dornyei’s taxonomy, the data was classified into thirteen strategies. A qualitative research was used as the method in this study and the data was collected by doing observation, audio recording and interviewing the teacher in SMAN 3 Banda Aceh. The result showed that eight strategies were used by the English teacher included three additional strategies that appeared during teaching process. Based on the result, stalling and time gaining strategy was the highest number of strategies used by the teacher in the classroom. Meanwhile the least number of strategies used was repetition. In addition, the teacher only implemented compensatory strategies in the class since the eight strategies were included into it. Therefore, it could be inferred that teacher who commonly applied compensatory strategies had high proficiency in English. Thus, by conducting this study, the teacher was expected to use and choose the best strategies to overcome the communication problem in the classroom.